KERJASAMA TIONGKOK - INDONESIA DALAM PERDAGANGAN DIGITAL (E-COMMERCE) PERIODE TAHUN 2017-2019 - Queen Lana Lavita, (2021)
Digitalization Economy is a phenomenon that present in this era of globalization as a result of technological innovations carried out from time to time. Countries in the world have used technology in their economic activities, including in international trade. The presence of technology makes international trade can be done easily through a platform that can be referred as e-Commerce. Indonesia as a developing country has practiced digital trade and has several platforms including Tokopedia, Shopee, Lazada, Bukalapak and so on. Indonesia, which is developing a digital economy, still has some difficulties to develop the e-Commerce. To overcome that, Indonesia cooperating with other countries, one of them is China. The two countries cooperate in the ACFTA and the Belt Road Initiative scheme. In its implementation, there are several impacts and obstacles. The purpose of this study is to explain how both countries implement the cooperation using the theory of bilateral cooperation, regional economic integration, digital economy and foreign direct investment. Using a qualitative research approach with the type of descriptive research. Through these theories and concepts, the results of research on the implementation of digital trade cooperation between Indonesia and China run in two forms, investment and ICT development, and in which there are several impacts and obstacles in the course of cooperation.